Mitochondrial calcium exchange links metabolism with the epigenome to control cellular differentiation - Alyssa A. Lombardi (Nature Portfolio, 2019)
Myofibroblast differentiation contributes to extracellular matrix remodeling and fibrosis. Here, the authors report that alterations in mitochondrial calcium uptake is essential for metabolic reprogramming and epigenetic signaling for activation of the myofibroblast gene program.